1991
DOI: 10.1007/bf00655884
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced crosslinking: II. Effect on the crystalline and amorphous densities of polyethylene

Abstract: Small-angle x-ray scattering (SAXS) was used to determine the structural changes in polyethylene induced by radiation. The changes in densities of the crystalline and amorphous phases, pc and Pa, were calculated after direct determination of the 9 9 2 ...... mean square denszty fluctuatzon < 7? >. pa increases with increasing radiation dose for both linear and branched polyethylene. This accounts for the serious discrepancy between crystallinities determined from wide-angle x-ray scattering and density measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…PHB and PHBV produced similar carbonyl radical anion and various carbon radicals via abstracting primary, para, and tertiary hydrogen when subjected to γ‐radiation at 77 K. Chain crosslinking would therefore happen between these radicals to increase the molecular weight. The scission of the polyester chain occurred adjacent to the ester moiety, resulting in a decreasing molecular weight …”
Section: Pretreatment Methods To Introduce Reactive Functional Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…PHB and PHBV produced similar carbonyl radical anion and various carbon radicals via abstracting primary, para, and tertiary hydrogen when subjected to γ‐radiation at 77 K. Chain crosslinking would therefore happen between these radicals to increase the molecular weight. The scission of the polyester chain occurred adjacent to the ester moiety, resulting in a decreasing molecular weight …”
Section: Pretreatment Methods To Introduce Reactive Functional Groupsmentioning
confidence: 99%
“…The scission of the polyester chain occurred adjacent to the ester moiety, resulting in a decreasing molecular weight. [54,55] Both reactions take place primarily in the amorphous region, while some may occur in the boundary between the crystalline and amorphous regions. [56] The scission reaction via γradiation could significantly reduce the onset degradation temperature and the temperature of the maximum weightloss rate of PHBV.…”
Section: Gamma Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…These defects can serve as sites for subsequent crosslinking. Chen et al measured the density by SAXS and concluded that the density of the amorphous phase increases with dose whereas that of the crystalline phase remains essentially constant 15…”
Section: Pe Crosslinkingmentioning
confidence: 99%
“…The net effect on the network formation results from the two competitive and simultaneous mechanisms of crosslinking and bond scission 17. The introduction of metallocene copolymers of polyethylene of very low density brings new questions because not only the crystallinity is lower and less well organised (micelles and sometimes lamellae are present) but also the interfacial domains between crystalline and amorphous phases may play an important role 15…”
Section: Pe Crosslinkingmentioning
confidence: 99%